Transparency, Ethical Leadership, and Employee Trust: The Moderating Role of Collective Trust in Management - Ana Marcal; Baldric Siregar; Soegiharto Soegiharto; Wing W. Winarto; Alfredo Dos Santos (CV. Ulil Albab Corp, 2026)
In an increasingly complex business environment, trust plays a critical role in sustaining organizational systems and maintaining healthy relationships among employees. This study investigates how transparency and ethical leadership influence employee trust and examines the moderating role of collective trust in management (CTM) within the organizational context of Timor-Leste. This research based on survey data collected from 154 employees across 22 organizations. The findings reveal that both transparency and ethical leadership have a positive and significant effect on employee trust. However, collective trust in management negatively moderates these relationships. Practically, the findings emphasize the importance of consistent managerial practices particularly timely and transparent communication, as well as fair and ethical treatment of employees, in mitigating negative workplace perceptions and fostering sustainable organizational relationships.